2020
DOI: 10.1101/2020.05.03.20082818
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contact tracing and isolation of asymptomatic spreaders to successfully control the COVID-19 epidemic among healthcare workers in Milan (Italy)

Abstract: ObjectiveTo study the source, symptoms, and duration of infection, preventive measures, contact tracing and their effects on SARS-CoV-2 epidemic among healthcare workers (HCW) in 2 large hospitals and 40 external healthcare services in Milan (Italy) to propose effective measures to control the COVID-19 epidemic among healthcare workers. DesignEpidemiological observational study. SettingTwo large hospitals and 40 territorial healthcare units, with a total of 5700 workers. Participants143 HCWs with a SARS-CoV-2 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…In the Milan area, Northwestern Italy, 10% positive swabs were reported in the framework of contact tracing; no mass screening was carried out. Overall, 2.6% of positive cases were reported after "random testing" in HW [34].…”
Section: Discussionmentioning
confidence: 99%
“…In the Milan area, Northwestern Italy, 10% positive swabs were reported in the framework of contact tracing; no mass screening was carried out. Overall, 2.6% of positive cases were reported after "random testing" in HW [34].…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out in Milan on a large population including 5700 HCWs, the rate of positive nasopharyngeal swab was 10%, whereas the proportion of positive results was only 2.6% through random tested HCWs [12]. The lower proportion of positive HCWs identified in our study might be due both to misclassification of close contacts (some operators might have intentionally over reported the duration of the contact to receive the diagnostic swab) and to the lower incidence rate in the general population of Rome, compared to that of Milan in the same period.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 19 studies included, contact tracing of index patients who were identified as asymptomatic cases, according to our definition, was reported in nine (Table 1, Figure 1) (6,11,(19)(20)(21)(22)(23)(24)(25)). All except one tested all close contacts for SARS-CoV-2, regardless of symptoms (23 (21).…”
Section: Summary Of Secondary Attack Rates Of Asymptomatic Index Casesmentioning
confidence: 99%